Animal Models in Biomedical Research: Ethics and Alternatives - Kumar, Arun (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
Animal models have long been central to biomedical research, providing critical insights into disease mechanisms, pharmacological responses, and therapeutic outcomes. However, the ethical concerns surrounding animal experimentation have grown substantially, leading to debates over the necessity, justification, and humane treatment of animals in laboratories. This paper explores the role of animal models in modern biomedical science, scrutinizes ethical concerns, and evaluates emerging alternatives such as organoids, computer simulations, and in vitro systems. The study emphasizes the importance of adhering to the 3Rs principle—Replacement, Reduction, and Refinement—and assesses current global trends aimed at replacing animal models with more humane and technologically advanced methods.